2020
DOI: 10.1002/gdj3.111
|View full text |Cite
|
Sign up to set email alerts
|

Global database of diffuse riverine nitrogen and phosphorus loads and yields

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…However, the validity of their model might be questionable (and cannot be verified) because only a single train-test split was implemented in Damania et al (2019) , whereas we conducted the 10-fold cross-validation (repeated 3 times) as well as out-of-sample testing to validate our model performance. Another example is McDowell et al (2021) who used GEMStat database to build a multiple linear regression model for predicting NOx—N values globally (for 7 years; centered around 2008). Multiple linear regression achieved R 2 of 0.57, which is 36.7 % lower than our model performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the validity of their model might be questionable (and cannot be verified) because only a single train-test split was implemented in Damania et al (2019) , whereas we conducted the 10-fold cross-validation (repeated 3 times) as well as out-of-sample testing to validate our model performance. Another example is McDowell et al (2021) who used GEMStat database to build a multiple linear regression model for predicting NOx—N values globally (for 7 years; centered around 2008). Multiple linear regression achieved R 2 of 0.57, which is 36.7 % lower than our model performance.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the time dimension, we relied on a commonly used approach introduced by Cohn et al (1989) (also known as L7 model), where the constituent concentration is related to three explanatory variables: discharge, time, and season. Similar approach was implemented in some regression-based WQ models and it has been shown that this scheme can reasonably explain temporal variability in constituent concentrations ( Hirsch et al, 2010 ; McDowell et al, 2021 ). Therefore, we added two new auxiliary inputs, namely Cumulative Month since the beginning of the simulation (CM) and Month of the Year (MOY) to represent distance in the time domain, thereby better capturing dynamics of nitrogen levels.…”
Section: Methodsmentioning
confidence: 99%
“…(a) A table from Detrital zircon U–Pb geochronology and geochemistry of the Riachuelos and Palma Sola beach sediments, Veracruz State, Gulf of Mexico: a new insight on palaeoenvironment (Armstrong‐Altrin, 2020). (b) A table from Global database of diffuse riverine nitrogen and phosphorus loads and yields (McDowell et al, 2021).…”
Section: Challenges To Support Data Extraction Workflow For Scientifi...mentioning
confidence: 99%
“…When instantaneous water discharge and/or suspended sediment concentration and/or solution properties (T , pH, alkalinity, Si(OH) 4 , DIC, DOC, HCO − 3 , SO 2− 4 , Cl − , Ca 2+ , Mg 2+ Na + , K + , calcite saturation) were reported in the same study, these were also added for comparison. However, the focus of data collection remains on the composition of solid phases, and detailed information on water chemistry is available from other sources (Hartmann et al, 2014a;McDowell et al, 2020a;Virro et al, 2021). Doublings with entries of other databases were not checked.…”
Section: Data Collectionmentioning
confidence: 99%